Factors Related to Health-related Quality of Life in Parents of Children with Autism Spectrum Disorder - Tong-on, Marisa; Yunibhund, Jintana (Journal of Phrapokklao Nursing College, Chanthaburi, 2019)
This descriptive correlational research aimed to study health-related quality of life (HRQOL) and the relationship between various factors and HRQOL among parents of children with autism spectrum disorder (ASD). The subjects were 154 parents of children with ASD from the outpatient departments of hospital of the Department of Mental Health. The research instruments were composed of the personal data questionnaire, the behavior evaluation questionnaire with the reliability of .81, the Brief COPE with the reliability of .88, the family function questionnaire with the reliability of .84, the social support questionnaire with the reliability of .93, the caregiver burden scale with the reliability of .90, and the Short Form Health Survey (SF-36) with the reliability of .80. Data were collected from September, 2016 to March, 2017. Statistics used for data analysis included frequency, percentage, mean, standard deviation, Pearson’s product moment correlation coefficient, and Spearman’s rank correlation coefficient. The research results revealed that the overall mean score of HRQOL among parents of children with ASD was 63.25 (SD = 16.85). Behavioral problems of children with ASD and caregiver burden were negatively statistically significant related to HRQOL among parents of children with ASD (r = -.340, p < .001 and r = -.544, p < .001, respectively), whereas family function and social support of parents were positively statistically significant related to HRQOL among parents of children with ASD (r = .449, p < .001 and r = .431, p < .001, respectively). This research suggests that health care providers who provide care for parents of children with ASD should promote HRQOL focusing on mental dimension, enhancing family function and social support, and patient’s behavior modification.